Advances in brain vasopressin - Urban, Ivan Jaroslav Arnost; Burbach, Johannes Peter Henri, 1954-; Wied, David de (Progress in brain research, 1998)
Advances in Brain Vasopressin elucidates the functions of the regulatory peptide vasopressin in the nervous system, and reviews the current status of this field at different levels. It deals with the cell biology and anatomy of the neurons that produce vasopressin in the brain, and provides an overview on the receptors of vasopressin and the signal transduction pathways that they activate, including the cellular responses that are triggered by vasopressin. Reviews are presented on the modulation of behavior induced by vasopressin in a number of different contexts, such as sex-linked and steroid-dependent behaviors, social behaviors, and learning and memory. Furthermore, the volume deals with several controversial issues in the field by presenting overlapping chapters from different research groups in order to provide the reader with current views. Highly relevant and useful, for those working on this "first" neuropeptide, and for young investigators entering the field, and in addition, shows how important a multidisciplinary approach is to unravelling the function of a neuropeptide in the brain